Nanoparticle-modified monolithic pipette tips for phosphopeptide enrichment - Krenkova, Jana; Foret, Frantisek (Analytical and bioanalytical chemistry, 2013)
We have developed nanoparticle-modified monoliths in pipette tips for selective and efficient enrichment of phosphopeptides. The 5 μL monolithic beds were prepared by UV-initiated polymerization in 200 μL polypropylene pipette tips and either iron oxide or hydroxyapatite nanoparticles were used for monolith modification. Iron oxide nanoparticles were prepared by a co-precipitation method and stabilized by citrate ions. A stable coating of iron oxide nanoparticles on the pore surface of the monolith was obtained via multivalent electrostatic interactions of citrate ions on the surface of nanoparticles with a quaternary amine functionalized poly(2-hydroxyethyl methacrylate-co-ethylene dimethacrylate) monolith. Hydroxyapatite nanoparticles were incorporated into the poly(2-hydroxyethyl methacrylate-co-ethylene dimethacrylate) monolith by simply admixing them in the polymerization mixture followed by in situ polymerization. The nanoparticle-modified monoliths were compared with commercially available titanium dioxide pipette tips. Performance of the developed and commercially available sorbents was demonstrated with the efficient and selective enrichment of phosphopeptides from peptide mixtures of α-casein and β-casein digests followed by off-line MALDI/MS analysis.
Keywords: chromatografie; fosfopeptidy; Durapatite; Porosity; železité sloučeniny; poréznost; syntetické pryskyřice; kaseiny; Chromatography; Phosphopeptides; Resins, Synthetic; Caseins; Ferric Compounds; Nanoparticles; hydroxyapatit; nanočástice